Circuit system analysis for real-time acquisition of bio-signals. (2015) - Bhogeshwar, Sande Seema; Soni, M.K.; Bansal, Dipali
Around the globe many deaths are being reported every year due to poor health monitoring system in rural areas and un-affordability by the people in the semi-rural areas. However, the evolution of bio-signal processing techniques which is a computer-based, compact, non-invasive and battery powered bio-signal monitoring solution can be reached to address this issue. An attempt has been made in this paper to analyse the developed real-time, low-cost acquisition and monitoring system in ORCAD 16.3 software. It introduces detailed analysis and explanation of the hardware circuit used to effectively acquire real-time noise-free ECG signals. Also it is adjunct to the doctors for the diagnosis purpose. The system includes instrumentation amplifier, DC restoration circuit, integrator, right leg driven amplifier and notch filter. Further it can be interfaced to a computer using sound port as a serial interface between circuit and PC for analysis in terms of features extraction. The developed circuit is compact and handy with low power consumption which realises low-cost and real-time processing.